Microfluidic Manufacture of Solid Lipid Nanoparticles: A Case Study on Tristearin-Based Systems - Anderluzzi, Giulia; Perrie, Yvonne (Drug Delivery Letters, 2020)
Background: Solid lipid nanoparticles are lipid-based carriers that can be used for a range of drugs and biomolecules. However, most production methods currently used do not offer easy translation from laboratory preparation to scale-independent production. Objectives: Within this study, we have investigated the use of microfluidics to produce solid lipid nanoparticles and investigated their protein loading capability. In the development of this process, we have investigated and identified the critical process parameters that impact on the product attributes of the solid lipid nanoparticles. Methods: Solid lipid nanoparticles based on Tristearin and 1,2-Distearoyl-phosphatidylethanolaminemethyl- polyethyleneglycol conjugate-2000 were formulated using the NanoAssemblr® Benchtop system. The flow rate ratio, total flow rate and initial protein concentration were investigated as process parameters and the particle size, PDI, zeta potential, drug loading and drug release were measured as product attributes. Results: Our results demonstrate the suitability of microfluidics as a production method for solid lipid nanoparticles containing protein. In terms of key process parameters to consider, both the solvent to aqueous flow rate ratio and the total flow rate were shown to have a notable impact on particle size. Protein loading capacity was influenced by the solvent to aqueous flow rate ratio but was similar across all flow rates tested. Conclusion: Within this study, we outline a rapid and easy protocol for the scale-independent production of solid lipid nanoparticles. This process can support the rapid translation of production methods from bench to clinic.
Keywords: protein delivery